Geographical classification of Italian saffron (Crocus sativus L.) based on chemical constituents determined by high-performance liquid-chromatography and by using linear discriminant analysis. (1st December 2016) - D'Archivio, Angelo Antonio; Giannitto, Andrea; Maggi, Maria Anna; Ruggieri, Fabrizio
Highlights: 144 saffron samples coming from the main production areas of Italy were analysed. Statistical data treatment permitted geographical classification of Italian saffron. Saffron metabolites responsible for geographical discrimination were identified. About 88% of saffron samples produced in four areas of Central Italy were classified. Abstract: One hundred and forty-four Italian saffron samples produced in the years from 2009 to 2015 in five distinct areas located in four different regions, Abruzzo (L'Aquila), Tuscany (Florence), Umbria (Cascia and Città della Pieve) and Sardinia, have been analysed by high-performance liquid chromatography with diode array detection. Intensities of the chromatographic peaks attributed to crocins, safranal, picrocrocin and its derivatives and flavonoids were considered as variables in linear discriminant analysis to attempt geographical classification. The results revealed that spices produced at different sites of the Italian territory can be discriminated with good accuracy. The differentiation of saffron cultivated in Sardinia from those produced in Central Italy was mainly attributed to different contents of the most abundant crocins. Good differentiation of spices produced in close sites of Central Italy was also observed, 88% of validation samples being correctly classified; some minor crocins are responsible for such discrimination.